Association between altered tryptophan metabolism, plasma aryl hydrocarbon receptor agonists, and inflammatory Chagas disease - Ambrosio, Laura Fernanda (2023)
Introduction: Chagas disease causes a cardiac illness characterized by immunoinflammatory reactions leading to myocardial fibrosis and remodeling. The development of Chronic Chagas Cardiomyopathy (CCC) in some patients while others remain asymptomatic is not fully understood, but dysregulated inflammatory responses are implicated. The Aryl hydrocarbon receptor (AhR) plays a crucial role in regulating inflammation. Certain tryptophan (Trp) metabolites have been identified as AhR ligands with regulatory functions. Methods, results, and discussion: We investigated AhR expression, agonist response, ligand production, and AhR-dependent responses, such as IDO activation and regulatory T (Treg) cells induction, in two T. cruzi-infected mouse strains (B6 and Balb/c) showing different polymorphisms in AhR. Furthermore, we assessed the metabolic profile of Trp catabolites and AhR agonistic activity levels in plasma samples from patients with chronic Chagas disease (CCD) and healthy donors (HD) using a luciferase reporter assay and liquid chromatography-mass spectrophotometry (LC-MS) analysis. T. cruzi-infected B6 mice showed impaired AhR-dependent responses compared to Balb/c mice, including reduced IDO activity, kynurenine levels, Treg cell induction, CYP1A1 up-regulation, and AhR expression following agonist activation. Additionally, B6 mice exhibited no detectable AhR agonist activity in plasma and displayed lower CYP1A1 up-regulation and AhR expression upon agonist activation. Similarly, CCC patients had decreased AhR agonistic activity in plasma compared to HD patients and exhibited dysregulation in Trp metabolic pathways, resulting in altered plasma metabolite profiles. Notably, patients with severe CCC specifically showed increased N-acetylserotonin levels in their plasma. The methods and findings presented here contribute to a better understanding of CCC development mechanisms and may identify potential specific biomarkers for T. cruzi infection and the severity of associated heart disease. These insights could be valuable in designing new therapeutic strategies. Ultimately, this research aims to establish the AhR agonistic activity and Trp metabolic profile in plasma as an innovative, non-invasive predictor of prognosis for chronic Chagas disease.